Bhutan : Assessment Letter for the World Bank. (Policy Papers; Policy Paper, 2010)
Bhutan's growth was resilient to the financial crisis and the outlook remains positive. Containing fiscal expansion and enhancing liquidity management are necessary to avoid economic overheating. Strengthening bank supervision is also a top priority.